The Dialectics of Freedom of Expression and Legal Restrictions on Digital Platforms: An Analysis of Human Rights Principles, the Electronic Information and Transactions Law, and Constitutional Court Decision Number 105/PUU-XXII/2024 - Hanafi, Hanafi (Scholar Center, 2025)
The right to freedom of expression is a fundamental aspect of human rights, guaranteed by both the Indonesian Constitution and international human rights instruments. However, this freedom is not absolute and may be subject to restrictions through regulatory frameworks such as the Electronic Information and Transactions (ITE) Law. In practice, the application of the ITE Law has sparked controversy due to the vague and overly broad language of several provisions, leading to multiple interpretations and granting excessive discretionary power to law enforcement authorities and certain parties in controlling the dissemination of electronic information. This situation has resulted in numerous cases of criminalization, raising serious concerns about the shrinking democratic space in Indonesia. This study aims to examine the legal implications of Constitutional Court Decision Number 105/PUU-XXII/2024 in relation to freedom of expression and its limitation under the ITE Law. Employing a doctrinal legal research method with a conceptual and statutory approach, the study analyzes primary legal materials and human rights theories as its analytical framework. The findings indicate that the Court’s decision constitutes a critical corrective measure by limiting the subject of defamation offenses under the ITE Law solely to individuals. This interpretation strengthens the principle of lex certa (legal certainty), curtails arbitrary interpretation in law enforcement, and reinforces the protection of freedom of expression in the digital space. Moreover, it reflects a balanced approach between safeguarding individual rights and upholding the public interest in a democratic society.